GROWTH PERFORMANCE OF MAJOR CARP, LABEO ROHITA FINGERLINGS ON COMMERCIAL FEEDS - M. S. Ahmed; K. Shafiq; M. S. Kiani (Journal of Animal and Plant Sciences, 2012)
The influence of commercial feeds on growth performance of Labeo rohita (rohu) fingerlings was investigated in 42 days culture trials. Twenty fingerlings were maintained in well aerated 95 L glass tanks in triplicate. Three different commercial feeds, rice bran as control (T 1); Miracle (T 2) and Tokyo (T 3) were purchased from the local market. Fish were fed @ of 3 % of their wet body weight twice a day at 12 hours interval for 6 weeks. Fish growth parameters (length and weight) were taken weekly. The amount of feed was adjusted according to the average increase in biomass of fish in each tank of all treatments. There was a significant increase (P<0.05) in average wet body weight, FCR and gross fish production of fish fed with Tokyo (T 3) when compared with Miracle (T 2) and rice bran (T 1). These findings suggest that Tokyo appears to be sufficient for obtaining optimum growth in rohu.
Keywords: Pelleted feed efficacy; commercial artificial feed; growth performance; Labeo rohita; fingerlings.